2013
DOI: 10.7314/apjcp.2013.14.4.2407
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnosis Soy Food Intake and Breast Cancer Survival: A Meta-analysis of Cohort Studies

Abstract: Background and Objectives: Data on associations between soy food intake after cancer diagnosis with breast cancer survival are conflicting, so we conducted this meta-analysis for more accurate evaluation. Methods: Comprehensive searches were conducted to find cohort studies of the relationship between soy food intake after cancer diagnosis and breast cancer survival. Data were analyzed with comprehensive meta-analysis software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 36 publications
2
72
0
1
Order By: Relevance
“…43 A meta-analysis of five prospective cohort studies from the United States and China found that high consumption of soy protein or soy isoflavones after breast cancer diagnosis was associated with a 26% decrease in recurrence (HR 0.74, 95% CI 0.61-0.85) and a 16% reduction in breast cancer mortality (HR 0.84, 95% CI 0.71-0.99) compared with low consumption. 44 Another meta-analysis of four prospective cohort studies, two of which were included in the previous analysis, found a 16% reduced risk of recurrence among women consuming high levels of soy isoflavone (RR 0.84, 95% CI 0.65-0.86), with no significant heterogeneity among the studies. 45 Interestingly, in both meta-analyses, soy intake was not associated with improved survival or reduced recurrence among premenopausal women or patients who used tamoxifen, which suggests that soy and tamoxifen may work through a similar mechanism of displacing estrogen from its receptor.…”
Section: Soymentioning
confidence: 99%
See 1 more Smart Citation
“…43 A meta-analysis of five prospective cohort studies from the United States and China found that high consumption of soy protein or soy isoflavones after breast cancer diagnosis was associated with a 26% decrease in recurrence (HR 0.74, 95% CI 0.61-0.85) and a 16% reduction in breast cancer mortality (HR 0.84, 95% CI 0.71-0.99) compared with low consumption. 44 Another meta-analysis of four prospective cohort studies, two of which were included in the previous analysis, found a 16% reduced risk of recurrence among women consuming high levels of soy isoflavone (RR 0.84, 95% CI 0.65-0.86), with no significant heterogeneity among the studies. 45 Interestingly, in both meta-analyses, soy intake was not associated with improved survival or reduced recurrence among premenopausal women or patients who used tamoxifen, which suggests that soy and tamoxifen may work through a similar mechanism of displacing estrogen from its receptor.…”
Section: Soymentioning
confidence: 99%
“…45 Interestingly, in both meta-analyses, soy intake was not associated with improved survival or reduced recurrence among premenopausal women or patients who used tamoxifen, which suggests that soy and tamoxifen may work through a similar mechanism of displacing estrogen from its receptor. 44 In some studies, the apparent benefit of soy was confined to patients with estrogen-receptor-positive tumours. Phyto estrogens bind to some estrogen receptors to mimic estrogen, whereas others antagonize and block the receptors; however, the selectivity of soy isoflavones is still not well understood.…”
Section: Soymentioning
confidence: 99%
“…The proliferative effect of soy isoflavones was mainly observed in animal models of tumours. However; paradoxically, consumption of phytoestrogens has also been associated with reduced risk of breast cancer [42][43][44][45][46] . This controversy with regard to the effect of soy isoflavones on breast cancer risk was analyzed and it was demonstrated that soy isoflavone phase Ⅱ metabolism differs between humans and rodents, and this should be taken in count to understand the value of the use of these rodents for investigate the effects of isoflavones in humans [47] .…”
Section: Nutrtion and Breast Cancermentioning
confidence: 99%
“…In addition, reduction in fat intake may help a breast cancer survivor to lose weight [16], which helps to improve disease-free survival. Finally, diets high in soy are linked to a decrease in both breast cancer recurrence and breast cancer mortality [31][32][33][34]. Finally, it is important to understand eating habits in order to find patterns that may lead to overeating when food cravings hit.…”
Section: Nutrition Recommendationsmentioning
confidence: 99%